2003
DOI: 10.1002/adma.200305618
|View full text |Cite
|
Sign up to set email alerts
|

Barrier‐Free Electron–Hole Capture in Polymer Blend Heterojunction Light‐Emitting Diodes

Abstract: Organic semiconductors fabricated as thin-film light-emitting diodes, LEDs, now provide a promising new display technology.[1] Solution-processed semiconductor polymers make possible direct printing (using ink-jet deposition) and allow high-resolution full-color displays to be conveniently manufactured. [2] Multiple-layer deposition, used in vacuum-sublimed molecular semiconductor LEDs, is difficult to achieve by solution processing. We have instead fabricated distributed heterojunction' structures that are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
324
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(344 citation statements)
references
References 31 publications
18
324
1
1
Order By: Relevance
“…Morteani et al have studied polymer:polymer blends and have shown with temperaturedependent measurements that energy transfer from the CT state dominates below 4V, with an endothermic activation energy of 200 meV ± 50 meV. [51][52][53] Since all of the presented EL spectra have been measured at voltages smaller than 4 V, this would suggest that the principal mechanism is energy transfer from the CT state to a component singlet. The activation energy of 200 meV corresponds to about twice the width of the density of states (DOS) of an organic semiconductor, 54 which may suggest that singlet emission is linked to an overlap of CT state emission and singlet absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Morteani et al have studied polymer:polymer blends and have shown with temperaturedependent measurements that energy transfer from the CT state dominates below 4V, with an endothermic activation energy of 200 meV ± 50 meV. [51][52][53] Since all of the presented EL spectra have been measured at voltages smaller than 4 V, this would suggest that the principal mechanism is energy transfer from the CT state to a component singlet. The activation energy of 200 meV corresponds to about twice the width of the density of states (DOS) of an organic semiconductor, 54 which may suggest that singlet emission is linked to an overlap of CT state emission and singlet absorption.…”
Section: Discussionmentioning
confidence: 99%
“…This loss mechanism, however, can be reduced by reducing the electronic coupling matrix element V * by, for example, increasing the distance between donor and acceptor molecule. However, decreasing V * will unavoidably result in a decrease in electron transfer rate, which is proportional to (V * ) 2 . 32 The analysis presented above allows experimental determination of V * , which we find is ∼6 meV for the TQ1:PCBM system studied in this work.…”
Section: Implications For Polymer:fullerene Photovoltaics and Concmentioning
confidence: 99%
“…32 The analysis presented above allows experimental determination of V * , which we find is ∼6 meV for the TQ1:PCBM system studied in this work. Assuming that this is a typical value for polymer:fullerene systems, a lower limit for the ratio between the molar extinction coefficient of CT absorption and pure polymer absorption can be calculated: Assuming intensity borrowing as the only cause for CT absorption, a ratio α CT /αD * = (V * ) 2 (E D * −E CT ) 2 between 10 −2 and 10 −4 can be calculated for E D * − E CT between 0.06 and 0.6 eV, typical energy offsets for organic photovoltaic applications. For finely intermixed systems, given a sufficiently high sensitive technique, this means that CT absorption bands will always be detectable if E CT is lower than E D * and V * is sufficiently large.…”
Section: Implications For Polymer:fullerene Photovoltaics and Concmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorene-triarylamine copolymers are specifi cally designed to be amorphous, with high glass transition temperatures, for use as interlayer and hole transport layer materials in polymer light emitting diodes. [31][32][33][34][35][36][37] They have also been used, along with the homopolymer poly(triarylamine), as p-type semiconductors in OFETs, allowing highly uniform charge transport over large-area substrates, an important requirement for applications such as display backplanes. [ 38 ] Their charge transport has been extensively studied in bulk diodes using the time-of-fl ight (TOF) and transient SCLC dark injection (DI) techniques, [39][40][41][42] and modeled in the low chargecarrier density regime using the GDM, correlated GDM, and polaronic correlated GDM.…”
Section: Introductionmentioning
confidence: 99%